Oral Pseudomembrane Kandidiasis in Nasopharynx Cancer - A Case Report - Siti Rusdiana Puspa Dewi; Shania Tri Maulina (Journal of Indonesian Dental Association, 2025)
Introduction. Nasopharyngeal cancer (NPC) is a malignant condition of the nasopharynx. The cancer therapy given is usually radiotherapy (RT), chemotherapy (CT), or a combination of RT and CT. Cancer therapy and poor oral hygiene can lead to susceptibility to fungal infections, one of which is pseudomembranous kandidiasis (thrush). The aim of this report was to present oral pseudomembrane kandidiasis patient with nasopharynx cancer. Case report. A 52-year-old female patient was referred to the hospital's dental clinic with complaints of a white coating on the inside of her cheeks, roof of the mouth, and tongue since Â± 1 week ago. The patient feels pain when swallowing and discomfort when opening the mouth. The results of clinical and supporting examinations showed that the patient was diagnosed with oral pseudomembranous kandidiasis. The patient was treated using nystatin drop and chlorhexidine gluconate 0.2% Conclusion. The NPC patient in this case was diagnosed with pseudomembranous kandidiasis (thrush) caused by Candida albicans. Early management of cases of pseudomembranous kandidiasis in NPC patients was very important so that the lesion would not disrupt the general condition of the patient as a whole. Collaboration and coordination from various specialist divisions were needed.